Serological response after COVID-19 infection compared to vaccination against COVID-19 in children with autoimmune rheumatic diseases - Tjaša Šinkovec Savšek; Mojca Zajc Avramovič; Tadej Avčin; Miša Korva; Tatjana Avšič-Županc; Nataša Toplak (BMC, 2024)
Abstract Background Paediatric patients with autoimmune rheumatic diseases (pARD) have a dysregulated immune system, so infections present a major threat to them. To prevent severe COVID-19 infections we aimed to vaccinate them as soon as possible. Studies have shown that the BNT162b2 vaccine is safe, effective, and immunogenic, however, in a short observation period, only. Methods The main objective was to compare the serological response between three groups of pARD: after SARS-CoV-2 infection, after vaccination against COVID-19 with two doses of the BNT162b2 vaccine, and after experiencing both events. Data on demographics, diagnosis, therapy, and serology (anti-SARS-CoV-2 IgG/IgA) were collected from March 2020 to April 2022. For statistical analysis ANOVA, Mann-Whitney U test, Chi-square test and Fisher's exact test were applied. To compare adverse events (AE) after vaccination we included a control group of healthy adolescents. Results We collected data from 115 pARD; from 92 after infection and 47 after vaccination. Twenty-four were included in both groups. Serological data were available for 47 pARD after infection, 25 after vaccination, and 21 after both events. Serological response was better after vaccination and after both events compared to after infection only. No effect of medication on the antibody levels was noted. The safety profile of the vaccine was good. Systemic AE after the first dose of the vaccine were more common in healthy adolescents compared to pARD. In the observation period of 41.3 weeks, 60% of vaccinated pARD did not experience a symptomatic COVID-19 infection. Conclusions IgG and IgA anti-SARS-CoV-2 levels were higher after vaccination and after both events compared to after infection only. Six months after vaccination we observed an increase in antibody levels, suggesting that pARD had been exposed to SARS-CoV-2 but remained asymptomatic. Trial registration The study was approved by the Medical Ethics Committee of the Republic of Slovenia (document number: 0120-485/2021/6).